Modelling the Spatio-Temporal Distribution of Ambient Nitrogen Dioxide and Investigating the Effects of Public Transit Policies on Population Exposure. (May 2017) - Shekarrizfard, Maryam; Faghih-Imani, Ahmadreza; Tetreault, Louis-Francois; Yasmin, Shamsunnahar; Reynaud, Frederic; Morency, Patrick; Plante, Celine; Drouin, Louis; Smargiassi, Audrey; Eluru, Naveen; Hatzopoulou, Marianne
Abstract: Estimating the future state of air quality associated with transport policies and infrastructure investments is key to the development of meaningful transportation and planning decisions. This paper describes the design of an integrated transportation and air quality modelling framework capable of simulating traffic emissions and air pollution at a refined spatio-temporal scale. For this purpose, emissions of Nitrogen Oxides (NOx ) were estimated in the Greater Montreal Region at the level of individual trips and vehicles. In turn, hourly Nitrogen Dioxide (NO2 ) concentrations were simulated across different seasons and validated against observations. Our validation results reveal a reasonable performance of the modelling chain. The modelling system was used to evaluate the impact of an extensive regional transit improvement strategy revealing reductions in NO2 concentrations across the territory by about 3.6% compared to the base case in addition to a decrease in the frequency and severity of NO2 hot spots. This is associated with a reduction in total NOx emissions of 1.9% compared to the base case; some roads experienced reductions by more than half. Finally, a methodology for assessing individuals' daily exposure is developed (by tracking activity locations and trajectories) and we observed a reduction of 20.8% in daily exposures compared to the base case. The large difference between reductions in the mean NO2 concentration across the study domain and the mean NO2 exposure across the sample population results from the fact that NO2 concentrations dropped largely in the areas which attract the most individuals. This exercise illustrates that evaluating the air quality impacts of transportation scenarios by solely quantifying reductions in air pollution concentrations across the study domain would lead to an underestimation of the potential health gains. Highlights: An integrated transportation, emissions, air quality modelling chain is developed. Our modelling framework is able to account for the spatio-temporal distribution of NO2 . The modelling framework was used to test the effect of transit investments. Increased transit service was associated with reductions in population exposure to NO2 .